First high resolution study of the pentad bending bands of deuterated silane: Energy structure of the (0200), (0101) and (0002) vibrational states of 28SiD4, 29SiD4 and 30SiD4. (October 2021) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Raspopova, N.I.; Kuznetsov, A.V.; Leroy, C.; Sydow, C.; Bauerecker, S.
Highlights: FTIR spectra of the 2 ν 2, ν 2 + ν 4, and 2 ν 4 bands of 28 SiD 4, 29 SiD 4, and 30 SiD 4 are recorded. "Hot" pentad–dyad transitions are assigned. Band centers, rotational, centrifugal distortion and resonance interaction parameters of the bending vibrational states. Abstract: The infrared spectra of SiD 4 in natural abundance were measured in the region of 350–2050 cm − 1 with a Bruker IFS 125HR Fourier transform interferometer at an optical resolution of 0.0021 and 0.0016 cm − 1 and analyzed. Not less than 6490 transitions with J max = 33 were assigned for the first time to the bands 2 ν 4, ν 2 + ν 4, and 2 ν 2 of the 28 SiD 4 molecule. Numerous "hot" dyad–pentad transitions (in general, 5545 "hot" transitions) were also assigned for the first time in the region of 600–760 cm − 1 . Rotational, centrifugal distortion, tetrahedral splitting, and interaction parameters for the ( 0002, F 2 ), ( 0002, E ), ( 0002, A 1 ), ( 0101, F 2 ), ( 0101, F 1 ), ( 0200, A 1 ) and ( 0200, E ) vibrational states were determined from the fit of experimental line positions. The obtained set of 69 fitted parameters reproduces the initial experimental data with an accuracy of d rms = 3.12 × 10 − 4  cm − 1 for the 6490 "cold" transitions and d rms = 2.33 × 10 − 4  cm − 1 for the 5545 "hot" transitions. Results of the analogues analysis for the 29 SiD 4 and 30 SiD 4 isotopologues with 403/136 "cold" and 171/99 "hot" assigned transitions are presented also.